(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
In children, attention begins to develop very early. Although one- or two-week-old infants show no signs of attention, they soon begin to show signs of voluntary attention, starting at one month of age. This article discusses the development of attention in children and ways and means to stabilize it.